Maßnahmen zur Hebung des Standes. Strategien von Unternehmern des Vergnügungsgewerbes am Beispiel des Leipziger Krystall-Palastes. - Dietze, Antje (Deutsches Institut für Urbanistik, 2019)
In the decades from the 1880s to the First World War, the Krystall-Palast in Leipzig was one of the outstanding institutions of popular entertainments in the German Empire. The article uses this example to discuss the factors enabling the emergence of urban amusement palaces and their corresponding transnational networks. It analyses the strategies used by entrepreneurs, managers, and investors to institutionalize this business while also improving their own social standing. They appropriated models of entertainment from Paris and London, reorganized the Krystall-Palast as a joint-stock company, and embedded it into financing networks and trade associations. Eventually, the article shows how these actors established the connections, institutions and social recognition that the cultural economy of a modem city such as Leipzig needed to take shape.
Keywords: Vergnügungsstätte; Multifunktionshalle; Massenkultur; Stadtkultur; Kommerzialisierung; Unternehmensstrategie; Stadtgeschichte; Unterhaltungsindustrie